(untitled) (Global Journals of Research in Engineering, 2016)
The changing scenario of the wireless connectivity has insisted the usage of the spectrum in an efficient manner which in turn demands for the new paradigms to be adopted in practice. The Cognitive Radio (CR) termed by Joseph E Mitola III in 1999, a prominent technology to overcome the above difficulty which continuously monitors the spectrum and allocates the un used portions of the spectrum to other users in a systematic approach. The most important task in this context is the design of the antenna to cater the needs of the CR networks and they must adapt the changes in the environment and must be reconfigurable.